2012
DOI: 10.1002/sim.5538
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of a decreasing hazard of patients with acute coronary syndrome

Abstract: The Kaplan-Meier, Nelson-Aalen and Breslow estimators are widely used in the analysis of right-censored time to event data in medical applications. These methods are fully non-parametric and do not put any restriction on the shape of the hazard curve. In some applications, this leads to implausible estimates of the hazard course over time. With non-parametric shape-constrained estimation techniques, one can facilitate an increasing or decreasing hazard and thus generate estimators that better match the biologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
9
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…Although the most attractive property of this approach is that it does not assume any fixed shape on the hazard curve, there are several cases where order restrictions, such as monotonicity, better match the practical expectations. An example can be found in van Geloven et al (2013), and other references therein, concerning a large clinical trial for patients with acute coronary syndrome that exhibit a decreasing risk pattern. Traditional nonparametric estimators, such as the Kaplan-Meier, Nelson-Aalen, or Breslow estimator, do not incorporate a decreasing risk pattern, and a monotone nonparametric estimate of the hazard rate is called for.…”
Section: Introductionmentioning
confidence: 99%
“…Although the most attractive property of this approach is that it does not assume any fixed shape on the hazard curve, there are several cases where order restrictions, such as monotonicity, better match the practical expectations. An example can be found in van Geloven et al (2013), and other references therein, concerning a large clinical trial for patients with acute coronary syndrome that exhibit a decreasing risk pattern. Traditional nonparametric estimators, such as the Kaplan-Meier, Nelson-Aalen, or Breslow estimator, do not incorporate a decreasing risk pattern, and a monotone nonparametric estimate of the hazard rate is called for.…”
Section: Introductionmentioning
confidence: 99%
“…Often it is natural to assume that the function λ 0 is monotone. For example, the risk of a second event for patients with acute coronary syndrome is expected to be decreasing over time because the conditions of patients stabilize as a result of the treatment and the natural disease course (van Geloven et al, 2013). Moreover, in van Geloven et al (2013) it is shown that using nonparametric shape constrained techniques leads to more accurate estimators than the traditional ones.…”
Section: Introductionmentioning
confidence: 99%
“…For example, the risk of a second event for patients with acute coronary syndrome is expected to be decreasing over time because the conditions of patients stabilize as a result of the treatment and the natural disease course (van Geloven et al, 2013). Moreover, in van Geloven et al (2013) it is shown that using nonparametric shape constrained techniques leads to more accurate estimators than the traditional ones. Estimation of the baseline hazard function under monotonicity constraints has been studied in Chung and Chang (1994), Lopuhaä and Nane (2013b), Lopuhaä and Musta (2017, 2018), where pointwise rates of convergence and limit distributions have been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Initially, the attention was on the derivation of large sample properties of the maximum partial likelihood estimator of the regression coefficients and of the Breslow estimator for the cumulative baseline hazard (e.g., see Efron, ; Cox, ; Tsiatis, ). Although the most attractive property of this approach is that it does not assume any fixed shape on the hazard curve, there are several cases where order restrictions better match the practical expectations (see van Geloven, , for an example of a decreasing hazard in a large clinical trial for patients with acute coronary syndrome). Estimation of the baseline hazard function under monotonicity constraints has been studied in Chung & Chang () and Lopuhaä & Nane ().…”
Section: Introductionmentioning
confidence: 99%